EFFECT OF FEEDING WHOLE OR GROUND PEARL MILLET (Pennisetum glaucum) WITH OR WITHOUT ENZYME SUPPLEMENTATION ON THE EGG QUALITY OF LAYING JAPANESE QUAILS (Coturnix coturnix japonica) - Sabo, M. N.; Duru, S.; Afolayan, S. B. (FUDMA JOURNAL OF SCIENCES, 2020)
The effects of dietary inclusion level (50% or 100%), form (whole or ground), and enzyme supplementation (with or without) of pearl millet at the expense of maize on the egg quality of laying Japanese quails was evaluated in this experiment. One hundred and sixty two female Japanese quails of seven weeks of age were used in a 2 x 2 x 2 factorial arrangement in a completely randomized design with eight treatments and a control all replicated thrice with 6 quails per replicate. Three fresh eggs were randomly picked from each replicate fortnightly starting from the 8th week for the measurement and determination of the following egg quality parameters; egg weight, shell weight, albumen weight, yolk weight, shell thickness and Haugh unit. Results of the study showed that completely replacing maize with whole or ground pearl millet wit-h or without enzyme supplementation increased the egg weight and reduced the Haugh unit of laying Japanese quails. Albumen and yolk percentages increased when 50% pearl millet was fed and decreased with the feeding 100% pearl millet. Feeding ground pearl millet and feeding pearl millet without enzyme supplementation decreased yolk percentage. The feeding of whole pearl millet with or without enzyme supplementation increased shell thickness, while shell weight, shell percentage, albumen weight and yolk weight were not affected by those factors